A study of platelet disorders in pregnancy - Pandey, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombocytopenia is low platelet count, if present during pregnancy can jeopardize the maternal and fetal outcome. Thrombocytopenia affects 6-15% of pregnancies. Causes of thrombocytopenia include gestational, idiopathic thrombocytopenia, preeclampsia, HELLP, DIC, malignancy and marrow failure. We planned to do this study to find out common causes of thrombocytopenia in our hospital and management being used. Methods: Data was collected form those women who came to the antenatal clinic (booked) and labour room (unbooked) in the department of obstetrics and gynaecology, Sir Sunder Lal hospital, institute of medical sciences, Banaras Hindu University. Data of a total of 67 pregnant women were collected during the period of July 2012 to June 2015. Results: There were 74.62% cases of gestational thrombocytopenia, 10.44% related to preeclampsia, 4.47% in Eclamptic patients, 1.49% in HELLP and DIC, 5.97% in ITP, and lastly 1.49% in malaria cases. There were number of associated complication whether directly related (PPH) or part of the disorder. PPH was observed in 22.38% which is maximum among all complications. Other complications were part of major associated illness i.e. liver failure (7.46%), renal failure (4.47%), DIC (4.47%) and HELLP (7.46%). Conclusions: Mode of delivery was not influenced by platelet count, but for obstetric indications. Management of patients was as per the diagnosis. Single donor plasma is preferable to random donor plasma. PPH was the commonest complication and we should be wary of that.